Different media, same relationships: What the Iris Piano Trio learned from the COVID-19 pandemic. (1st December 2021) - Latessa, Lauren; Oh, Jiyoung
The Iris Music Project is a non-profit dedicated to reimagining residential and healthcare communities as spaces of creative exchange. By February 2020, our chamber music group, the Iris Piano Trio, had developed a model for music programming at Charles E. Smith Life Communities (CESLC) in Rockville, Maryland (United States), that emphasized collaborative relationships between professional musicians and community members. The COVID-19 pandemic severely disrupted the Trio's work and tested its model. In this article, we describe how the Trio remained connected and relevant to CESLC residents by experimenting with virtual programmes that adapted our model to a digital setting. We argue that our prior relationships with residents and staff enabled us to impact their lives throughout the pandemic despite the isolation created by COVID-19 closures. The pandemic strained, but did not fundamentally change, the Trio's ensemble-in-residence model, suggesting its potential as a generalized model in the field of music and health.